Use of convalescent serum reduces severity of COVID-19 in nonhuman primates - Cross, Robert W.; Prasad, Abhishek N.; Borisevich, Viktoriya; Woolsey, Courtney; Agans, Krystle N.; Deer, Daniel J.; Dobias, Natalie S.; Geisbert, Joan B.; Fenton, Karla A.; Geisbert, Thomas W. (Cell reports (Cambridge), 2021)
Passive transfer of convalescent plasma or serum is a time-honored strategy for treating infectious diseases. Human convalescent plasma containing antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently being used to treat patients with coronavirus disease 2019 where clinical efficacy trials are ongoing. Here, we assess therapeutic passive transfer in groups of SARS-CoV-2-infected African green monkeys with convalescent sera containing either high or low anti-SARS-CoV-2 neutralizing antibody titers. Differences in viral load and pathology are minimal between monkeys that receive the lower titer convalescent sera and untreated controls. However, lower levels of SARS-CoV-2 in respiratory compartments, reduced severity of virus-associated lung pathology, and reductions in coagulopathy and inflammatory processes are observed in monkeys that receive high titer sera versus untreated controls. Our data indicate that convalescent plasma therapy in humans may be an effective strategy provided that donor sera contain high anti-SARS-CoV-2 neutralizing titers given in early stages of the disease. [Display omitted] •Treatment with convalescent sera mitigates COVID-19 severity in nonhuman primates•Sera with high SARS-CoV-2 neutralizing antibody titers show the greatest benefit•Data suggest passive transfer as a therapy in humans in early stages of disease Rapid development of postexposure therapies is necessary for emerging viral threats such as SARS-CoV-2. Cross et al. demonstrate therapeutic reduction of disease severity using convalescent sera with high concentrations of SARS-CoV-2 neutralizing antibodies in the African green monkey model of COVID-19, suggesting this as a possible treatment approach in humans.